2017
DOI: 10.1073/pnas.1715499114
|View full text |Cite
|
Sign up to set email alerts
|

Harmful algal blooms in the Eastern North Atlantic Ocean

Abstract: a Applying a mathematical model to the period 1982-2016 propose that ocean warming has expanded the niche for harmful algal blooms (HABs) of the species Dinophysis acuminata and Alexandrium fundyense, which can generate shellfish toxicity and pose risks to human health. The authors' model predicts an increase in the growth rate and in the duration of the bloom season for these species, with a "hot spot" being the North Eastern Atlantic (NEA) and North Sea (NS) waters surrounding the United Kingdom. Using ships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…Dinophysis presented the greatest bloom frequency. The countrywide interannual patterns observed are consistent with abundance observations at two targeted locations on the west coast of Scotland (Swan et al, 2018) and offshore patterns found in the Northeast Atlantic from Continuous Plankton Recorder data (Dees et al, 2017), and do not confirm the model based predictions of Gobler et al (2017) of a climate driven increase in the abundance of Dinophysis acuminata in the region. The monthly and annual Dinophysis analysis using K-means categories, determined that the blooms respond similarly between clusters at a regional scale, but with varying levels of risk.…”
Section: Temporal and Spatial Bloom Dynamicscontrasting
confidence: 66%
See 2 more Smart Citations
“…Dinophysis presented the greatest bloom frequency. The countrywide interannual patterns observed are consistent with abundance observations at two targeted locations on the west coast of Scotland (Swan et al, 2018) and offshore patterns found in the Northeast Atlantic from Continuous Plankton Recorder data (Dees et al, 2017), and do not confirm the model based predictions of Gobler et al (2017) of a climate driven increase in the abundance of Dinophysis acuminata in the region. The monthly and annual Dinophysis analysis using K-means categories, determined that the blooms respond similarly between clusters at a regional scale, but with varying levels of risk.…”
Section: Temporal and Spatial Bloom Dynamicscontrasting
confidence: 66%
“…The occurrence, intensity and distribution of HABs is a problem worldwide (Hallegraeff, 1993(Hallegraeff, , 2010Van Dolah, 2000;Smayda, 2002;Glibert et al, 2005;Anderson et al, 2017;Gobler et al, 2017;Wells et al, 2019). However, trends of increasing HAB frequency and/or abundance are not evident in all studies (Moore et al, 2009;Díaz et al, 2016;Dees et al, 2017) suggesting that local or regional variability is likely in any overall trend. This is consistent with recent results from Hallegraeff et al (2021) who used a metaanalysis of Harmful Algae Event Database and Ocean Biodiversity Information system data to demonstrate that there is no empirical support for a global increase in HAB events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a modelling study, Gobler et al [ 36 ] proposed that ocean warming had increased the growth rate and duration of the bloom season of D. acuminata over the period 1982–2006 in the North East Atlantic around the UK. However, following analysis of data from the Continuous Plankton Recorder (CPR) from the region, Dees et al [ 37 ] did not find any increase in the number or annual duration of Dinophysis blooms. While the greatest number of D. acuminata above threshold counts occurred in each of the last three years (2015–2017), our results ( Figure 2 and Figure 5 ), albeit over a shorter timescale than that modelled by Gobler et al [ 36 ], concur with the conclusion that there is no clear temporal increase in D. acuminata blooms.…”
Section: Discussionmentioning
confidence: 99%
“…Links between increasing sea surface temperatures and wind intensity have led to an increase in the potentially toxic diatom Pseudo-nitzschia in the NEA since the mid-1990s (Hinder et al, 2012). Climate change effect on the timing and severity of toxic events is still uncertain (Wells et al, 2019) with model predictions and in situ data not always coinciding (Dees et al, 2017;Gobler et al, 2017).…”
Section: Future Considerations For Early Warning Systemsmentioning
confidence: 99%